Joint photon-number splitting attack on semi-quantum key distribution - Mi, Shang; Dong, Shuang; Hou, Qincheng; Wang, Jindong; Yu, Yafei; Wei, Zhengjun; Zhang, Zhiming (Frontiers in Physics, 2022)
Semi-quantum key distribution is based on the basic principle of quantum mechanics, which makes the classical user and quantum user realize the information theory secure shared key. In 2021, Our research group proved the first proof-of-principle experimental demonstration of semi-quantum key distribution and verified its feasibility. Due to the limitations of existing science and technology, the experimental system is still a combination of multi-photon signal source and loss in the transmission line. This makes semi-quantum key distribution as susceptible to photon-number splitting attack as quantum key distribution, leads to limitations of secure transmission distance. It seems like that in practical single-state semi-quantum key distribution can overcome photon-number splitting attack due to the SIRT bits (also known as the “sifted key”). But its dual-channel feature still opens up an observation window to Eve. We present two joint photon-number-splitting attacks suitable for single-state semi-quantum key distribution system and show that through the joint PNS attack, Eve can obtain the key information without being detected by Alice and Bob.